Tolerance of Pedunculate oak (Quercus robur) saplings to herbicides - Laclau, Pablo (2020)
Spraying herbicides to reduce weed competition is a usual practice in agricultural regions. However, tree tending under agroforestry or forest plantations is hampered by the extensive use of these pesticides. Here, we assessed the survival, symptoms expression and growth of pedunculate oak (Quercus robur) saplings after spraying different herbicides at recommended doses in two seasons: winter and spring. Three independent herbicide trials were carried out on oak sapling plots (E_WINTER 2013, E_SPRING 2012, E_SPRING 2013) in Ayacucho, province of Buenos Aires, Argentina. Plants were kept under uniform conditions in a nursery for about three months. We alternatively tested the herbicides (doses in sub-index, cc.ha-1 or g.ha-1) flumioxazin (FLUM100), glyphosate (GLIF2000, 4000, 6000), metsulfuron-methyl (METS8), dicamba (DIC120), propaquizafop (PROP500, 1000), flurochloridone (FLUO1000, 1500, 4000), atrazine (ATR2000, 4000), acetochlor (ACET2000), imazethapyr (IMAZE500, 1000) and imazapyr (IMAZA33, 100). At the end of each trial all plants survived, regardless of treatment, although the symptoms varied depending on the trial and product. Glyphosate associated with chlorosis, necrosis and deformation, propaquizafop with necrosis, and dicamba, flurochloridone, imazethapyr and imazapyr with chlorosis. ATR2000 and FLUO1500 treatments advanced the re-sprout phases. In terms of growth, saplings sprayed with IMAZE1000, IMAZA100 and GLIF6000 had lower total dry weight than the control (CT) (p<0.05), in E_SPRING 2012. In E_WINTER 2013 differences of dry weight were not significant, but in E_SPRING 2013, FLUO1500 sprayed saplings had a lower dry weight of roots than CT (p<0.05). Total plant height and stem diameter presented similar trends. According to the whole set of symptoms assessed, the application of FLUM100, ACET2000, ATR2000 or METS8 would be compatible with oak saplings production. The low effect of herbicides in wintertime might be related to different ways of avoidance to herbicide penetration: root depth, the absence of foliage or to the protective structure of buds (perulae); in spring, to root depth, leaf cuticle thickness and hairiness, and to the (high) capacity of the oaks to re-sprout. Although the results obtained are promising for oak plantation in sites exposed to common herbicides, further research is needed to assess long term responses, or to repeated applications over time.